Trichothecium pseudoroseum sp. nov. (Myrotheciomycetaceae, Hypocreales) From Asia Revealed by Morphology and Multigene Phylogeny - Muhammad Binyamin Khan; Najam‐ul‐Sehar Afshan; Muhammada Jabeen; Muskan Amjad; Sardar Ali; Entaj Tarafder; Samantha C. Karunarathna; Ting Chi Wen (New Zealand Journal of Botany, 2026)
Trichothecium pseudoroseum sp. nov. is described from Yunnan Province, China, and Azad Jammu & Kashmir, Pakistan, based on morphological characteristics and multigene phylogenetic analyses. It is distinguished by its conidiophores, which arise directly from the substrate, are unbranched, solitary, long, slender, septate, slightly curved, smooth‐walled, and hyaline; the conidiogenous cells are smooth, hyaline, located at the apex, slightly swollen, and monoblastic, producing conidia that are ellipsoid, oblong, or pyriform in shape, asymmetrical, one‐septate, and smooth‐walled. To confirm its taxonomic placement, a multigene phylogenetic analysis based on Large Subunit and Internal Transcribed Spacer sequences was conducted, confirming it as an undescribed species and naming it as T. pseudoroseum . The fungus was isolated from the leaves of Trifolium sp., representing the first report of a Trichothecium species on this host. A full description, illustrations, and phylogenetic analysis results for T. pseudoroseum are provided, with comparisons to closely related taxa. This finding extends the known host range of T. pseudoroseum and provides new insights into its biodiversity and interactions with the Trifolium sp.